CHARACTERIZATION OF BACTERIA Salmonella sp. ON BROILER CHICKEN MEAT MARKETED AT SUKARAMAI MARKET, MEDAN CITY - Rangkuti, Marlinda Nilan Sari; Pulungan, Ahmad Shafwan S; Silaban, Friend (JBIO: jurnal biosains (the journal of biosciences), 2023)
One effort to meet high protein needs is obtained from chicken meat. Chicken meat is a food source that is composed of various nutritional values in balanced proportions. There is still doubt about Boiler Chicken meat being sold for sale because it is suspected that there is contamination with pathogenic microbes that can cause disease in humans. There is a risk that broiler chicken meat will be contaminated due to poor market sanitation. The aim of this research was to determine the bacterial contamination of Salmonella sp. in broiler chicken meat and the number of Salmonella sp bacteria. Which is found in samples of broiler chicken meat marketed at the Sukaramai Market, Medan City. This research method is a quantitative descriptive approach. This research was carried out at the Regional Health Laboratory of North Sumatra Province in May-June 2023. In this study, sample culture was carried out by streaking on Salmonella Shigella Agar (SSA) media, while the Total Plate Count (TPC) test for Salmonella sp. using pour plate media. The results showed that all 9 samples contained Salmonella sp. with the amount of bacterial contamination, namely A1 3.0 × 10-4, A2 3.9 × 10-4, A3 4.7 × 10-4, B1 4.0 × 10-4, B2 5.3 × 10-4, B3 6.0×10-4, C1 4.5×10-4, C2 6.8×10-4, C3 7.7×10-4. Based on the National Chicken Meat Standardization Agency ICS No. 67-120-20. In 2009, the maximum limit for microbial contamination and the maximum limit for residues in food ingredients of animal origin must not contain Salmonella sp.